IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI 7 PRABUMULIH - Hasanah Hasanah (Conciencia, 2015)
Portrait of teaching in junior high school (SMP) State 7 Prabumulih less to optimize the development of the capabilities of learners, both concerning the idea, feeling, and intention, as well as learners, lack the opportunity for critical thinking, logical, creative, and innovative. The research reveals the problem of how the planning process, implementation, and enabling and inhibiting factors Education Unit Level Curriculum (KTSP) on the subjects of Islamic Education (PAI) in SMP Negeri 7 Prabumulih. This article is the result of research by the author in the first semester of the school year 2012/2013 in SMP Negeri 7 Prabumulih. These results indicate that the SMP Negeri 7 Prabumulih already implemented models Education Unit Level Curriculum (KTSP) on the subjects of Islamic education in SMP Negeri 7 Prabumulih accordance with the procedure determined and the learning process that consisted of the initial activities, the core, and the cover is in conformity with the preparation of a pre-planning and previous learning.